STUDI EVALUASI PELAKSANAAN PROGRAM CORPORATE FARMING DI KABUPATEN GROBOGAN - Suminah, Suminah; Utami, Bekti Wahyu (AGRITEXTS: Journal of Agricultural Extension, 2004)
This research aim is to know: (1) activities of Corporate Farming (CFIPCF) Program; (2) ementary and resistor factors in activities of CF/PCF Program, and (3) result, impact and benefit of CF/PCF policy. This research is executed in Grobogan District, that is: in villages which CF1 PCF Program were conducted. This study represent ek.splorative-evaluative research. Data were taken by: (a) Observation in field; (b) Interview with various source (.r;takeholders) which is related to CF1 PCF program execution. Data and all information obtained were analysed quantitatively and also qualitatively. Result in this research is: (I) Concept of CF can not be executed by fully yet in Grobogan District because it was not disagree with local society culture; (2) In farm, CF I PCF has degraded the cost product farm, farming efficiency progressively was supported by mechani=e which reduce on processing, planting, crop expense and treatment of.farm cost; (3) Adoption of CFIPCF technology has been executed although not fully; (4) CFIPCF management can not arrange member yet according to CFIPCF recommendation, specially in the.field of marketing; (5) Bargainning position of CFPCF in the off-farm field is still not yet gratified, reasonable price (~f farming product is not yet competent to farmer. Also, networking system in product marketing is stil/ 1,,veak.